Genome-wide epigenetic profiling and transcriptome analysis in pediatric Obstructive Sleep Apnea: A focus on Black female children - Bala S.C. Koritala; Sreeja Parameswaran; Omer A. Donmez; Carmy Forney; Hope Rowden; Charles A. Moore; Angela L. Duggins; Alexandra Sestito; Brittany A. Leader; Matthew T. Weirauch; Leah C. Kottyan; David F. Smith (Heliyon)
Obstructive Sleep Apnea (OSA) is a common sleep-related breathing disorder characterized by airway obstruction during sleep. Diagnosing pediatric OSA is challenging, particularly in underrepresented populations, leading to disparities in treatment and long-term negative health outcomes. Our study aimed to identify alternative diagnostic tools by investigating genome-wide epigenetic changes and associated transcriptomic alterations in Black female, pediatric patients with OSA. Whole-genome bisulfite sequencing and RNA sequencing were performed on saliva samples from healthy controls and children with OSA. Analysis of differential methylation and gene expression patterns revealed dysregulated inflammation and metabolism pathways in children with OSA. Chromosomes 19 and 22 exhibited elevated methylation signatures in this patient population. Integration of methylation and gene expression data identified specific molecular markers, including NAP1L4, CCR1, and LIF. The study emphasizes the need to consider both genetic and environmental factors in pediatric OSA, and the identified markers may offer avenues for further research.